Identification and characterization of iron acquisition systems in Stenotrophomonas maltophilia - Vasodavan, Kalidasan (2017)
Iron plays an essential role in bacterial pathogenesis most importantly shaping hostpathogen interactions. Host intracellular iron concentration not only serves as a signal for regulating the expression of iron acquisition systems in bacteria but also induce the secretion of a number of toxins and virulence factors in most pathogenic species. On the other hand, iron acquisition systems also act as candidates for prophylactics and therapeutics. A recently emerged environmental origin Gram-negative nosocomial pathogen Stenotrophomonas maltophilia, which is resistant to most antimicrobial agents pose major public health problems particularly among severely debilitated and immunocompromised individuals. Iron has shown to regulate biofilm formation, oxidative stress response and several pathogenic mechanisms in S. maltophilia. The present study is aimed at identifying various iron acquisition systems and iron source utilized during iron starvation in S. maltophilia. The complete genome K279a, R551-3, D457 and JV3 were annotated through “Rapid Annotations using Subsystems Technology” (RAST) to identify putative iron acquisition systems. Polymerase chain reaction (PCR) assay was used to screen different targets involved in the iron acquisition systems. In order to investigate the effect of iron depletion and iron repletion on various genotypic and phenotypic properties of S. maltophilia, the isolates were subjected to iron starvation by growing in brain heart infusion (BHI) broth supplemented with the iron chelator, 100 μM 2,2’- dipyridyl (BHI-DIP) while for iron-repleted condition, BHI-DIP was supplemented with 100 μM FeCl3. The iron acquisition genes expression under different iron conditions was investigated using NanoString Technologies. The production of siderophore in S. maltophilia was assessed by using “CAS agar diffusion (CASAD)” and FeCl3 test. The spectrophotometric colorimetric assays such as Atkin’s assay and Arnow’s assay were performed in order to detect the chemical nature of siderophore. Utilization of hemin, hemoglobin, transferrin and lactoferrin during iron depletion in S. maltophilia was measured by growth kinetics.The annotation of the complete genome K279a, R551-3, D457 and JV3 using RAST identified two putative subsystems involved in iron acquisition such as “Iron siderophore sensor & receptor system” and “Heme, hemin uptake and utilization systems/hemin transport system”. Further molecular screening of each target revealed the clinical isolates contain complete putative targets in comparison with environmental isolates. The gene expression showed significant expression for FeSR, HmuT, Hup, ETFb, TonB and Fur under iron-depleted condition. S. maltophilia were found to produce catechol-type siderophores and utilized hemin, hemoglobin, transferrin and lactoferrin as iron sources. In conclusion, the data in this research put together gives preliminary information on the iron acquisition systems and iron source utilized by S. maltophilia recommending further investigation in understanding their roles in pathogenesis, drug and vaccine development.